Faktor Yang Memengaruhi Perilaku Santri Terhadap Kepatuhan Pola Hidup Bersih Sehat Di Pondok Pesantren Ulumul Qur'an Mardhatillah Kota Subulussalam - Risa Andriani; Ismail Efendy; Ramadhani Syafitri Nasution; Endang Maryanti; Asriwati Asriwati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Healthy students or Clean and Healthy Living Behavior (PHBS) Islamic boarding school settings are a combination of educational institutional settings and household settings aimed at cultivating PHBS for students. The aim to be achieved in this research is to determine and analyze the behavior of students towards complying with a clean and healthy lifestyle at the Ulumul Qur'an Mardhatillah Islamic boarding school, Subulussalam City. This type of research is a descriptive analytical survey with a cross sectional design. The research population was junior high school students at the Ulumul Qur'an Mardhatillah Islamic boarding school, Subulussalam City with a total of 132 students. sampling using the total population method. Data analysis was carried out using univariate, bivariate and multivariate analysis. Based on the results of the chi-square test, it is known that patient success has an influence on knowledge, attitudes, family support, infrastructure and teacher/cleric support with a value of p = 0.000, meaning that there is an influence of knowledge, attitude, family support, infrastructure and teacher/cleric support on adherence to a clean and healthy lifestyle. From the results of the multivariate analysis, it is known that the most influential variable in this study is the family support variable with an OR value of 6.020. The conclusion is that family support is the dominant factor influencing compliance with a clean and healthy lifestyle at the Ulumul Qur'an Mardhatillah Islamic boarding school, Subulussalam City.